Pelatihan Manajemen Kearsipan Modern pada Guru MPLB di Jawa Timur Menuju Pendidikan Inklusif dan Berdaya Saing - Farij Ibadil Maula; Brillian Rosy; Novi Trisnawati; Fitriana Rahmawati; Prisilia Joyceline Atmojo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
In the era of digital transformation, modern, systematic, and integrated archive management has become a crucial element in creating effective, efficient, and accountable education governance. Office Management and Business Services (MPLB) teachers in East Java still face obstacles in implementing technology-based archive management due to limited digital literacy, lack of supporting facilities, and minimal ongoing training relevant to 21st-century needs. This Community Service (PKM) activity aims to improve the professional competence of MPLB teachers in modern archive management through interactive workshop-based training, intensive mentoring, and direct simulation of the use of digital archiving applications. The implementation methods included participant needs analysis, problem-solving-based module development, digital archive management practice using a cloud system, and pre-test and post-test-based evaluation to measure competency improvement. The results of the activity showed an average increase in participant understanding of 42%, a 58% increase in operational skills in using archiving applications, and a 35% increase in archive management time efficiency. In addition, teachers are able to implement an electronic file classification system in schools and build a database of digitized documents. These activities strengthen transparent and sustainable educational administration, as well as supporting the realization of inclusive and globally competitive education in line with the Asta Cita vision towards Indonesia Emas 2030.